Fowler–Nordheim Tunnelling Contribution in AlGaN/GaN on Si (111) Schottky Current. Issue 1 (2nd January 2016) - Bag, Ankush; Das, Palash; Ghosh, Saptarsi; Mukhopadhyay, Partha; Dinara, Syed Mukulika; Kumar, Rahul; Chakraborty, Apurba; Biswas, Dhrubes
ABSTRACT: AlGaN/GaN heterojunction with Schottky metal contact can be modelled with two back-to-back diodes. The forward-biased diode between metal and AlGaN barrier acts at the onset of current with positive bias. Fowler– Nordheim tunnelling is mainly responsible for the electron transport at the low positive bias level. Downward energy band bending of AlGaN barrier with further positive voltage reduces the tunnelling probability due to lowering of the barrier height of the first diode, causing a dramatic change in the current.